2019
DOI: 10.1111/pce.13503
|View full text |Cite
|
Sign up to set email alerts
|

EgRBP42 from oil palm enhances adaptation to stress in Arabidopsis through regulation of nucleocytoplasmic transport of stress‐responsive mRNAs

Abstract: Abiotic stress reduces plant growth and crop productivity. However, the mechanism underlying posttranscriptional regulations of stress response remains elusive. Herein, we report the posttranscriptional mechanism of nucleocytoplasmic RNA transport of stress-responsive transcripts mediated by EgRBP42, a heterogeneous nuclear ribonucleoprotein-like RNA-binding protein from oil palm, which could be necessary for rapid protein translation to confer abiotic stress tolerance in plants. Transgenic Arabidopsis overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Our results provide functional evidence for mRNA nucleocytoplasmic dynamics regulating gene expression. On the one hand, and comparable to previous reports in yeasts and plants under stress conditions(Saavedra et al, 1996;Zander et al, 2016; Lee and Bailey-Serres, 2019;Yeap et al, 2019), we observed that mRNAs with critical biological functions (e.g., nitrate metabolism) are enriched in the cytoplasm, indicating their accumulation is favored to sustain translation of genes that play essential roles in response to the nutrient. On the other hand, we also identified enriched GO-terms associated with nitrogen processes (for example, nucleotide biosynthesis and…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Our results provide functional evidence for mRNA nucleocytoplasmic dynamics regulating gene expression. On the one hand, and comparable to previous reports in yeasts and plants under stress conditions(Saavedra et al, 1996;Zander et al, 2016; Lee and Bailey-Serres, 2019;Yeap et al, 2019), we observed that mRNAs with critical biological functions (e.g., nitrate metabolism) are enriched in the cytoplasm, indicating their accumulation is favored to sustain translation of genes that play essential roles in response to the nutrient. On the other hand, we also identified enriched GO-terms associated with nitrogen processes (for example, nucleotide biosynthesis and…”
supporting
confidence: 92%
“…In plants, the export-machinery components are more diverse than in yeast or animals (Yelina et al, 2010; Pfaff et al, 2018), suggesting their ability to regulate cytoplasmic mRNA levels in response to a stimulus is more versatile (Ehrnsberger and Grasser, 2019). Some studies have shown that subsets of mRNAs display particular nucleocytoplasmic distributions during different plant processes, such as cell cycle control (Yang et al, 2017), ethylene signaling (Chen et al, 2019), RNA-directed DNA methylation (Choudury et al, 2019), and stress response (Yeap et al, 2019). However, the mRNA nucleocytoplasmic dynamics at the genome-wide level have only been described in response to flooding stress (Lee and Bailey-Serres, 2019; Reynoso et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…EGRBP42 was a heterogeneous nuclear ribonucleoprotein-like RNAbinding protein from oil palm, which might enhance the resistance of plants to abiotic stresses by accelerating protein translation. The overexpression of EgRBP42 enhanced the resistance of transgenic Arabidopsis to abiotic stresses such as drought, cold, salt and flood, and enhanced the resilience after stress [48]. Based on these, EgDREB1 and EgRBP42 could be used as important candidate proteins for drought tolerance studies of oil palm.…”
Section: Molecular Biology Of Oil Palm With Drought Resistancementioning
confidence: 97%
“…With the advancement of molecular biology technology, distinct oil palm varieties are being explored from the molecular perspective to identify the genes related to the cold resistance of oil palm, providing a theoretical foundation for the breeding and selection of new varieties of oil palm. For instance, EgRBP42, which was a heterogeneous ribonucleoprotein RNA binding protein derived from oil palm, might regulate post-transcriptional processes of gene expression under abiotic stress conditions to enhance oil palm tolerance to cold [48]. The DREB subfamilies contain a single DNA-binding domain that acts as regulators of abiotic stress responses.…”
Section: Molecular Biology Of Oil Palm With Cold Resistancementioning
confidence: 99%
“…Especially, low temperature causes yellowing and withering of young leaves and flowers in oil palm. Various EgWRKY, DREB1, EgRBP42, EgEREBP and EgNAC genes were identified and characterized in oil palm under different abiotic stresses (Xiao et al 2017;Azzeme et al 2017;Yeap et al 2012Yeap et al , 2019Omidvar et al 2013). Base editing tool can be applied to edit endogenous WRKY DREB1, RBP42, EREBP and NAC genes for developing stress tolerant oil palm plants.…”
Section: Advantages and Prospective Genes For Base Editing In Oil Palmmentioning
confidence: 99%